2014
DOI: 10.1002/2013gb004679
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability and anthropogenic change in equatorial Pacific surface ocean pCO2 and pH

Abstract: The equatorial Pacific is a dynamic region that plays an important role in the global carbon cycle.This region is the largest oceanic source of carbon dioxide (CO 2 ) to the atmosphere, which varies interannually dependent on the El Niño-Southern Oscillation (ENSO) and other climatic and oceanic drivers. We present high-resolution observations of surface ocean CO 2 partial pressure (pCO 2 ) at four fixed locations in the Niño 3.4 area with data sets encompassing 10 ENSO warm and cold events from 1997 to 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 79 publications
11
114
1
Order By: Relevance
“…Variability of 100-150 µatm is also common in the equatorial Pacific during the extension of the warm water pool during El Niño events on timescales of months and the passing of tropical instability waves on timescales of weeks (e.g., Fig. 4 in Sutton et al, 2014). Sustained, long-term mooring time series also provide the opportunity to identify and remove the short-term variability from the time series and investigate long-term trends.…”
Section: Data Description and Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability of 100-150 µatm is also common in the equatorial Pacific during the extension of the warm water pool during El Niño events on timescales of months and the passing of tropical instability waves on timescales of weeks (e.g., Fig. 4 in Sutton et al, 2014). Sustained, long-term mooring time series also provide the opportunity to identify and remove the short-term variability from the time series and investigate long-term trends.…”
Section: Data Description and Accessmentioning
confidence: 99%
“…Sustained, long-term mooring time series also provide the opportunity to identify and remove the short-term variability from the time series and investigate long-term trends. For example, in a synthesis of equatorial Pacific mooring data, Sutton et al (2014) found that the uptake of anthropogenic CO 2 and an acceleration in equatorial upwelling since the shift in the Pacific Decadal Oscillation in 1998 has led to high rates of pCO 2 change of +2.3 to +3.3 µatm yr −1 in this region. This decadal shift in CO 2 outgassing is consistent with underway pCO 2 observations made in this region since 1982 .…”
Section: Data Description and Accessmentioning
confidence: 99%
“…Basin-specific rates in the f CO 2 increase vary from 1.2 to 2.1 µatm yr −1 for the years 1970 to 2007 , with higher rates of 2.3 to 3.3 µatm yr −1 at different mooring sites in the equatorial Pacific Ocean for the more recent period of 1997 to 2011 (Sutton et al, 2014a). The annual pH decreases at rates of −0.0013 yr −1 in the South Pacific Ocean (for 1998 to 2012) to −0.0026 yr −1 in the Irminger Sea (for 1982 to 2006) , while annual pH changes vary from −0.0018 to −0.0026 yr −1 for moorings in the equatorial Pacific Ocean for 1997 to 2011 (Sutton et al, 2014a). Here it is worth noting that such rates of change vary with the start date and period used for the calculation as a result of interannual to decadal variability (McKinley et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…In the equatorial Pacific, using pCO 2 measurements made at four moorings and the relation of Lee et al (2006) to calculate alkalinity, Sutton et al (2014) detected a decreasing pH trend associated with anthropogenic CO 2 absorption but also due to increased upwelling.…”
Section: Introductionmentioning
confidence: 45%